FABRICATION, MORPHOLOGICAL AND OPTOELECTRONIC PROPERTIES OF ANTIMONY ON POROUS SILICON AS MSM PHOTODETECTOR - H. A. Hadi (Journal of Fundamental and Applied Sciences, 2015)
We report on the fabrication and characterization of MSM photodetector. We investigated the surface morphological and the structural properties of the porous silicon by optical microscopy, atomic force microscope (AFM) and X-ray diffraction. The metal–semiconductor–metal photodetector were fabricated by using Sb as Schottky contact metal.The junction exhibits good rectification ratio of 105 at bias of 2V. A large photocurrent to dark-current contrast ratio higher than 55 orders of magnitude and low dark currents below 0.89 nA .High   responsivity of 0.225A/W at 400 nm and 0.15 A/W at 400 and 700nm were observed at an operating bias of less than -2 V, corresponding quantum efficiency of 70% and 26% respectively. The lifetimes are evaluated using OCVD method and the carrier life time is 100 μs. The results show that Sb on porous silicon (PS) structures will act as good candidates for making highly efficient photodiodes.